[Black Student Union member sitting on chair]
The BSU member is seated on a wooden chair wearing knee high boots with buttons, a black skirt and vest, a white long sleeve shirt with a pattern on the elbow of the sleeve, and a black top hat. Photo taken during BSU's Heritage Week Fashion Show.